A experiência do usuário (UX) em interfaces gráfico-informacionais: um estudo de caso dos aplicativos de educação em saúde da UNASUS/UFMA - Castro Junior, Eurides Florindo de (2016)
In design, the act of projecting requires a systematization of steps that considers, among other factors, the research of similes, the definition of methodologies, materials, the functional aspects of the product, the user profile and the context of use. However, perceptual, emotional and attitudinal aspects of the human being are fundamental to obtain the efficiency, efficacy and satisfaction in design projects, and these have been little observed. Many projects designed to devise health education applications have prioritized technological and pedagogical aspects, thus minimizing the importance of design and the user itself in the process. On the scientific context, it is still possible to observe the lack of research addressing the User Experience (UX) in the context of mobile platforms for health education, most of the available literature presenting more generalistic findings on the subject of mobile platforms. Based on these aspects, this research employed descriptive and explanatory studies in order to assess UX graphic-informational interfaces of health education courses offered by means of applications. To outline its methodological procedures, it was taken in consideration the three key elements addressed by UX (efficiency, effectiveness and satisfaction). Thereby, the study was structured in 2 phases : (1) the Analytical Study and (2) the Interaction Test. In the first phase it was possible to understand the graphic-informational trends of the interfaces of the applications analyzed, as well as to identify the didactic content representative of the whole sample and that could be used on the Interaction Test. On the second phase, the Interaction Test listed the elements of the graphic interface and how they affect the UX. Although the post-task questionnaire has indicated a positive satisfaction of the doctors/participants on all aspects analyzed, it was observed that the reported problems were related to the efficiency element (usability), which were identified during the performance of the tasks proposed in the questionnaire. Besides that, doctors/participants reported problems related to the lack of standardization of the functions of interaction elements (clickable objects), as well as the large number of interactions necessary to complete some tasks (e.g. quitting the application). In another finding, it was found that the cognitive load brought by the user (knowledge and abilities), as well as its real context of interaction with digital gadgets, does interfere on the UX of graphic interfaces of applications designed for health education. Finally, as a contribution of the research, it is proposed recommendations to the design of graphic-informational interfaces aimed at health education.